KEANEKARAGAMAN SAPINDACEAE YANG DIMANFAATKAN SEBAGAI BUAH DI DESA GEGERUNG, KECAMATAN LINGSAR, KABUPATEN LOMBOK BARAT - Fathul Muin; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2025)
Gegerung is one of the villages in the Lingsar District, West Lombok Regency. The research was conducted using the observation method. Based on research, it is known that there are two species in the Sapindaceae family that are used as fruit, namely: Dimocarpus longan and Nephelium lappaceum.